SINTESIS DAN KARAKTERISASI KOMPLEKS Mn (II) DAN Zn (II) DENGAN KETOKONAZOL SERTA UJI AKTIVITAS TERHADAP Candida albicans - Fitri Handayani, Nurul
Ketoconazole is an antifungal that has antifungal activity against some fungal species, especially Candida albicans. In recent years, the synthesis of antibiotic complexes with metal had been reported. Ketoconazole also reported could be formed a complex with the metal ruthenium (II) which its activity was increased and the spectrum of activity also extended. This study aims to form complexes ketoconazole use other metals, namely Mn (II) and Zn (II) in order to obtain a better antifungal activity than ketoconazole base. In this experiment, the synthesis of ketoconazole complexes with these metals were done with reflux method. After the complexes were obtained, they were characterized by Fourier- Transform Infrared Spectroscopy (FTIR), UV-Vis Spectrophotometer, Thin Layer Chromatography (TLC), melting point test, Differential Scanning Calorimetry (DSC), and X-Ray Powder Diffractometry (PXRD). Furthermore, the complexes’s antifungal activity against Candida albicans ATCC 10231 were tested using cylinder plate method. Results of FTIR analysis from the complexes indicated that it had wavelength shift about 10-20 cm -1 in group C=N, C-O as compared to ketoconazole base. The UV spectrum of the complexes and ketoconazole base showed that the maximum wavelength of complexes were higher than wavelength of ketoconazole. TLC analysis were showed that the complexes only had one spot which indicated the complexes were pure. Ketoconazole had a melting point about 145- 147 °C, while the melting point of the ketoconazole complex with manganese was 103-105 °C and ketoconazole complex with zinc was 133-135 °C. Results of DSC indicated that the ketoconazole had endothermic peak at 140-160,5 °C and exothermic peak at 324-365,8 °C. The ketoconazole complex with manganese had endothermic peak at 105-166,9 °C and exothermic peak at 320,6-364,9 °C. Then ketoconazole complex with zinc had no endothermic peak. The ketoconazole complex with zinc only had exothermic peak at 106,3- 166,6 °C and 326,2-365,2 °C. Then, results of PXRD were showed that the ketoconazole complexes with Mn and Zn had amorphous form, in contrast to ketoconazole base which had crystalline peaks in its difractogram. After the complexes were characterized, the complexes were tested antifungal activity against Candida albicans ATCC 10231. The results showed that the activity of the complexes with Mn (II) and Zn (II) were higher than ketoconazole base. In conclusion, the ketoconazole complexes with Mn (II) and Zn (II) can be formed using methods reflux. Complexes has different physicochemical characteristics as compared to ketoconazole base. The activity of ketoconazole complexes againts Candida albicans ATCC 10231 are higher than ketoconazole base. Complex with Mn (II) has potency 1,44 fold higher than ketoconazole base and itself Zn (II) has potency 1,40 fold higher than ketoconazole base.